Factors Influencing Procrastination of Grade 12 Humanities and Social Sciences Students of Bestlink College of the Philippines: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The deliberate delay of obligations or decisions is known as procrastination. It is a commonproblem that many people deal with on a daily basis, and it can be problematic. In light of thiscircumstance, the researchers decided to carry out this study to learn more about how factorssuch as motivation and discipline influence students to procrastinate. The Pickle Jar Theory,which Jeremy Wright developed, served as the foundation for the study. The study'srespondents will be Grade 12 Humanities and Social Sciences students who are enrolled inthe 2022–2023 academic year.. The variable motivation is categorized as "Influential" as a factor that contributes to students'procrastination. The variable discipline is considered "Highly Influential" as a factorcontributing to students' procrastination. Results show that discipline and motivation areregarded as "Highly Influential" factors contributing to student procrastination.The researchers conclude that the majority of the study's respondents are female studentsaged between 17-18 years old. The leading factor that contributes to students' procrastinationis discipline, which is interpreted as "Highly Influential." followed by motivation, which isinterpreted as "Influential." To be more productive and feel in control of obligations,researchers advise students to work in a calm environment, eliminate needless tasks, create alist of tasks, and acquire good time management. Researchers also encourage students to beorganized and make goals in order to stay motivated to reach their objectives. After finishing atask, students can treat themselves, which is an excellent way to increase motivation.
Keywords: Education